ISLAMIC BUSINESS ETHICS IN THE MARKETING MODEL SHOPEE AFFILIATE - Adilah Salma; Shely Intan Agvela; Muhibban (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This journal aims to find out how the shopee affiliate marketing model is from the perspective of Islamic business ethics. Basically, Islamic business ethics play an important role in the shopee affiliate program. Shopee affiliate users need to follow Islamic values and Islamic principles that govern business behavior based on the teachings of Islam. In running the business, it is necessary to look at the selection of halal products, convey honest information, conduct business with integrity, and distribute commissions fairly. In addition, shopee affiliate users should also pay attention to how they promote their products. They should avoid sales tactics that deceive or manipulate consumers. By applying Islamic business ethics in the shopee affiliate program, users can run their business with blessings and have a positive impact in society. The method used in this journal is a normative perspective approach that focuses based on certain norms, moral values, or ethical standards. The results that have been obtained from this are that shopee affiliates have applied the principles of Islamic business ethics. From this shopee affiliate program, there are many positive influences on the community to continue to develop business through the shopee marketplace.